Comparison of the incidence and causes of injuries in stand-up and ground combat-sport fighters – a narrative review - Gastoł, Bartłomiej; Mikołap, Karolina; Staroń, Arkadiusz; Kras, Marta; Karkos, Patrycja; Kuśmierczyk, Katarzyna; Jurga, Marta (Quality in Sport, 2024)
Injuries in combat sports can happen to any athlete, regardless of gender, age, training experience or whether he or she is an amateur or a professional. The range of injuries varies from superficial, short-term damage to severe injuries with serious consequences, including death. There are many types of combat sports, each with different rules and specific injuries. Amongst various divisions of combat sports, one of the basic ones is the division into ground and stand-up sports. In the following work, using the available literature, we wanted to present the specifications of several of the most popular combat sports and compare their most common locations of injuries, types of injuries and mechanisms of their formation, paying attention to which of these categories a given sport belongs to. We also discuss differences in the rate of injury for different age, genders, prevalence of injuries during situations of practice and competition. In the end, it is presented what are the possible long-term complications of injuries in combat sports and which actions such as protective gear, bans on certain techniques or behavioural changes might reduce the injury rate to protect the athletes health, well-being and decrease the economic burden on healthcare systems.